Patient-reported perceptions of life quality and longevity in chronic heart failure - Lubis, Ahmad Feriansyah; Lubis, Anggia Chairuddin; Andra, Cut Aryfa; Raynaldo, Abdul Halim; Ardini, Tengku Winda; Haykal, Teuku Bob; Sarastri, Yuke (Heart Science Journal, 2025)
BACKGROUND: Although heart failure therapy has advanced, many patients still experience functional limitations, which impact their quality of life. OBJECTIVES: To explore the factors influencing heart failure patients' preferences for quality of life and longevity. METHODS: This cross-sectional study was conducted at Adam Malik Hospital, Medan, Indonesia. The study was conducted from April 2023 to October 2023. A total of 143 chronic heart failure patients were included using purposive sampling. Data were collected through interviews and the EuroQol five-dimension five-level questionnaire, EuroQol visual analogue scale, and the Time Trade-Off method. Statistical analysis was performed using multivariate logistic regression. RESULTS: Of the 143 patients, 66.4% preferred quality of life over longevity, and 47.3% were willing to trade two years of their lives for a better quality of life. The main factors associated with this preference were heart failure with reduced ejection fraction (OR: 3.554; 95% CI: 1.373 - 9.198; p: 0.009), diabetes mellitus (OR: 2.705; 95% CI: 1.108 - 6.602; p: 0.029), and lower visual analog scale scores (OR: 0.889; 95% CI: 0.848 - 0.932; p: 0.000). Our results also showed that patients in the longevity group had better ejection fractions, fewer rehospitalizations, and were less likely to have diabetes mellitus or chronic kidney failure compared to the quality of life group. CONCLUSION: The majority of heart failure patients choose quality of life over longevity, and this may be influenced by symptom burden and rehospitalization history. These findings emphasize the importance of patient-centered therapy focusing on symptom management and psychosocial support.